Hubungan Antara Status Gizi, Gula Darah Sewaktu Dengan Tekanan Darah - Cahyaningrum, Ika; Cita, Errick Endra; Dewi, Novita; Supriyadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Hypertension is a disease that causes morbidity and mortality in Indonesia. According to Riskesdas in 2018 the incidence of hypertension in East Java was 36.6%, this figure increased compared to 2013 (26.4%). The aim of this research is to analyze the relationship between nutritional status, temporary blood sugar and blood pressure.Method: This type of research is analytic observational with a cross sectional approach. The object of this study was the community of RW 12 Oro Ombo Village who took part in a health examination and were willing to be examined. The technique of taking research subjects with total sampling, with a total of 54 people. This research was carried out at RW 12 Oro Oro Ombo Village, Batu City in January 2022. Data in the study were obtained through measurements of research subjects by measuring body weight and height, as well as blood sugar when carried out using POCT (Point Of Care Testing) while measuring blood pressure by measuring systolic blood pressure using a digital sphygmomanometer.Result: The results obtained from this study were that there was no relationship between nutritional status and blood sugar when the p value = 0.156 (> 0.05) and there was a relationship between blood sugar levels when and systolic blood pressure of the people of RW 12 Oro Oro Ombo Village, Batu City, p value = 0.024 ( <0.05). For health workers, the hope is to encourage the public to routinely check their health at health service facilities to detect their health status early.Conclusion: The reseach showed that there was no relationship between nutritional status and temporary blood sugar, but there was a significant relationship between temporary blood sugar levels and systolic blood pressure in the community of RW 12 Oro Oro Ombo Village, Batu City.